Pembentukan Karakter Anak Usia Dini melalui Permainan Tradisional Balogo - Fajriani, Kartika; Pancasilawati, Abnan; Hasmawaty, Hasmawaty; Liana, Heppy (Antroposen: Journal of Social Studies and Humaniora, 2022)
This study aims to determine the stages and rules of the game, as well as the values of character education contained in the traditional Balogo game from South Kalimantan Province. The approach in this research is a qualitative approach. The subjects in this study were students who were in Kindergarten institutions ranging in age bfrom 6-7 years. Data collection techniques used are observation, interviews, and documentation. The collected data is processed through data reduction, data presentation, data classification, and drawing conclusions. The results showed that the traditional Balogo game played by Kindergarten students aged 6-7 years consisted of 8 stages of the game and 8 game rules. The values ​​of character beducation in the Balogo game include: honesty, tolerance, discipline, hard work, independence, democracy, love for the homeland, respect for achievement, friendly/communicative, peace-loving, social bcare, and responsibility